Severe Persistent Hyponatremia: A Rare Presentation of Biliary Fluid Loss - Kichloo, Asim (J Investig Med High Impact Case Rep, 2019)
Hypotonic hyponatremia is caused by a serum sodium level of <135 mEq/L in the setting of excess solute loss accompanied by free water retention because of antidiuretic hormone release, subsequent to decreased effective arterial blood volume. Acute hyponatremia can have various neurological manifestations, including drowsiness, lethargy, coma, seizures, respiratory depression, and even death. In this article, we present a case of a 41-year-old man who presented with hyponatremia as a result of sodium containing biliary fluid loss and resultant renal free water retention in response to increased antidiuretic hormone secretion. He underwent placement of a cholecystostomy tube for acalculous cholecystitis and was found to be persistently hyponatremic despite repletion with sodium-containing fluids. Once the cholecystostomy tube was removed, the patient’s sodium levels improved, and his symptoms resolved. Our case highlights choleuresis as an unusual but significant cause of hyponatremia in patients who have external biliary drainage.